Acute neurotoxicity evaluation of two anticholinesterasic insecticides, independently and in mixtures, and a neonicotinoid on a freshwater gastropod. (February 2021) - Herbert, Lucila Thomsett; Cossi, Paula Fanny; Painefilú, Julio César; Mengoni Goñalons, Carolina; Luquet, Carlos Marcelo; Kristoff, Gisela
Abstract: Neurotoxic insecticides are ubiquitous in aquatic ecosystems, frequently as part of complex mixtures. Freshwater gastropods are generally underrepresented in neurotoxicity evaluations and cumulative toxicity testing. This study investigates the behavioural and biochemical effects of acute exposures to the carbamate carbaryl, the organophosphate chlorpyrifos, and the neonicotinoid acetamiprid on the freshwater gastropod Chilina gibbosa . First, we evaluated behavioural neurotoxicity and cholinesterase (ChE), carboxylesterase (CE), and glutathione S-transferase (GST) activities in acute (48h) single-chemical exposures to increasing concentrations of carbaryl (0.5–500 μg L −1 ), chlorpyrifos (10–7500 μg L −1 ), and acetamiprid (1–10000 μg L −1 ). We then studied the effects of acute (48h) exposures to binary mixtures of carbaryl and chlorpyrifos equivalent to 0.5, 1, and 1.5 ChE 48h-IC50 . None of the insecticides caused severe behavioural neurotoxicity, except for a significant lack of adherence by 5000 μg L −1 chlorpyrifos. Carbaryl caused concentration-dependent inhibition of ChEs (NOEC 5 μg L −1 ; 48h-IC50 45 μg L −1 ) and CEs with p-nitrophenyl butyrate as substrate (NOEC 5 μg L −1 ; 48h-IC50 37 μg L −1 ). Chlorpyrifos caused concentration-dependent inhibition of ChEs (NOEC 50 μg L −1 ; 48h-IC50 946 μg L −1 ) but did not affect CEs (NOEC ≥7500 μg L −1 ). Carbaryl-chlorpyrifos mixtures inhibited ChEs additively, inhibited CEs with p-nitrophenyl butyrate, and did not affect behaviour. GST activity was not affected by single or mixture exposures. Acute exposure to acetamiprid did not affect any of the endpoints evaluated. This study provides new information on carbaryl, chlorpyrifos, and acetamiprid toxicity on C. gibbosa, relevant to improve gastropod representation in ecotoxicological risk assessment. Graphical abstract: Image 1 Highlights: Study of carbaryl, chlorpyrifos, and acetamiprid neurotoxicity on Chilina gibbosa . Carbaryl caused concentration-dependent inhibition of B-esterases. Chlorpyrifos produced concentration-dependent inhibition of cholinesterases. Carbaryl-chlorpyrifos mixtures inhibited B-esterases. Acetamiprid did not affect behaviour or enzymatic activity.